2022
DOI: 10.3389/fmed.2022.834805
|View full text |Cite
|
Sign up to set email alerts
|

Presbyopia-Correcting Intraocular Lenses Implantation in Eyes After Corneal Refractive Laser Surgery: A Meta-Analysis and Systematic Review

Abstract: PurposeTo assess the efficacy, safety, and predictability of presbyopia-correcting intraocular lenses (IOLs) in cataract patients with previous corneal refractive surgery.MethodsA systematic literature search was performed to identify studies evaluating the clinical outcomes of presbyopia-correcting IOLs implantation in cataract surgery after laser refractive surgery. Outcomes were efficacy, safety and predictability parameters.ResultsThe authors identified 13 studies, involving a total of 128 patients and 445… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Various refractive surgeries are used for presbyopia correction, including IOL implantation. Consequently, a number of studies have investigated the effectiveness of various IOLs in addressing presbyopia [ 54 , 55 ] . In addition, a study compared the clinical results of presbyopia-correcting IOLs that combine the extended depth of focus and bifocal profiles with a standard monofocal IOL [ 56 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Various refractive surgeries are used for presbyopia correction, including IOL implantation. Consequently, a number of studies have investigated the effectiveness of various IOLs in addressing presbyopia [ 54 , 55 ] . In addition, a study compared the clinical results of presbyopia-correcting IOLs that combine the extended depth of focus and bifocal profiles with a standard monofocal IOL [ 56 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Several emerging studies have highlighted the efficacy and safety of multifocal and EDOF IOLs in improving distance, intermediate and near vision, hence spectacle independence, in eyes with previous CRS (including myopic and hyperopic LASIK/PRK) when compared to monofocal IOLs [52,53 ▪ ,54]. A recent meta-analysis of 13 studies showed that presbyopia-correcting IOLs can result in spectacle independence for distance, intermediate and near vision in 98, 99 and 78%, respectively [55 ▪▪ ]. However, visual phenomena such as glare and halo are relatively common in patients who receive presbyopia-correcting IOL (around 30–40%) [55 ▪▪ ].…”
Section: Refractive Target and Spectacles Independencementioning
confidence: 99%
“…A recent meta-analysis of 13 studies showed that presbyopia-correcting IOLs can result in spectacle independence for distance, intermediate and near vision in 98, 99 and 78%, respectively [55 ▪▪ ]. However, visual phenomena such as glare and halo are relatively common in patients who receive presbyopia-correcting IOL (around 30–40%) [55 ▪▪ ]. It is also shown that EDOF IOLs may serve as a potential option for achieving spectacle independence in eyes with previous CRS unsuitable for multifocal IOLs [56].…”
Section: Refractive Target and Spectacles Independencementioning
confidence: 99%
“…With the advancements in refractive cataract surgery and the widespread adoption of presbyopia-correcting IOLs [ 1 ], patients with cataracts now have a broader range of options available. These options promise to provide spectacle independence across various distances, including far, intermediate, and near vision [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%